Il était une fois l'Ifremer - Chatry, Gilles (éditions Quae, 2021)
The development of sustainable fishing and aquaculture, interactions with climate change and the preservation of marine biodiversity place the oceans at the center of major issues. In the marine sciences landscape, Ifremer (French Research Institute for the Exploitation of the Sea) plays a central role. It is the only French research organization whose activities are all linked to the sea. Resolutely focused on the challenges to come, Ifremer is no less part of a story. This is the story that Gilles Chatry, archivist at Ifremer, wishes to share with the public for the first time. Created in 1984 from the merger between Cnexo and ISTPM, Ifremer has its roots in the more distant past, in the 19th century, when science invested in marine fisheries. By examining the archives of Ifremer in particular, the author sketches an unknown institutional history. As in a journal, the reader goes back in time, following key dates to the rise of modern oceanology. This is the genesis of this organization - outstanding personalities, ambitious scientific programs, new vessels and measuring instruments - that the author brings to life through his richly documented and illustrated story. Lovers of maritime history, oceanography and oceanology will find something to feed their curiosity there.